Echi di August Klingemann in Joseph von Eichendorff. «Viel Lärmen um Nichts» e l’eredità romantica: [Echoes of August Klingemann in Joseph von Eichendorff. «Viel Lärmen um Nichts» and the romantic heritage] (Studia theodisca, 2024)
This paper aims to investigate the presence of August Klingemann’s early Romantic «Musterroman» Romano (1800-1801) in Joseph von Eichendorff’s late Romantic tale Viel Lärmen um Nichts [Much Ado About Nothing]. Published in 1832, Viel Lärmen um Nichts provides insight into the ongoing decline of German Romanticism, by considering themes, characters and symbols of the Romantic movement – such as the role of subjectivity, dream and imagination – and highlighting their being out of place in dealing with the depiction of a changed historical and cultural context. While Eichendorff’s nostalgic view is displayed through the adventures of prince Romano, who embodies Romanticism in its anachronistic features, it is by means of Willibald and Aurora’s reunion at the end of the story that Eichendorff, in the final stage of his literary production, gives voice to his hope for a new dawn of Romantic poetry.